Studentsâ€™ Caring Attitudes to Wetland Environment: A Case of Environmental Education In Banjar District Indonesia (Jurnal Pendidikan IPA Indonesia, 2021)
Schools in Indonesia have been conducted environmental education programs through both curriculum activities and schoolsâ€™ environmental programs. However, there was no sufficient data about the effectiveness of the programs. This study aims to identify the junior high school studentsâ€™ caring attitudes to the wetland environment (CATWE) as the education outcome. The Six Junior High Schools were chosen as probability sampling areas classified as urban, central, and rural areas schools of Banjar District with total samples of 354 students aged 12-14 years. The CATWE data were collected using a valid and reliable questionnaire. This study found that most of the students care for the wetland environment. There were no differences in the CATWE of the three school areas. These findings indicate that the school area and the level of the â€œAdiwiyataâ€ program were not the primary determining variable of environmental caring attitude education effectiveness. The highest score of the CATWE indicator was responsible; meanwhile, the lowest was hard work. Even though all the indicators have reached a care category. It is necessary to thoroughly investigate the effectiveness of the school environmental program â€œAdiwiyata,â€ outside classroom activity, and family role in environmental education.